2022
DOI: 10.1111/ijsa.12361
|View full text |Cite
|
Sign up to set email alerts
|

The structured interview's resistance to gender discrimination under cognitive load

Abstract: Job interviews are cognitively demanding tasks for interviewers. However, it is unclear whether the high cognitive load (CL) that interviewers face will ultimately compromise the resistance to discrimination that otherwise distinguishes structured interviews from other selection methods. Using a two-study experimental design, we explored the effect of cognitive load on gender discrimination in structured job interviews. In Study 1, participants completed an online interview simulation in which they assessed bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
3
0
2
Order By: Relevance
“…It is possible that these components of structure were sufficient to diminish any advantage of self-promotion for men. Indeed, past research has found that structured interviews are fairly resistant to gender bias (Alonso et al, 2017; Kith et al, 2022; Pogrebtsova et al, 2020) overall; it appears that structure may also make the interview more resistant to differential effects of self-promotion tactics.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these components of structure were sufficient to diminish any advantage of self-promotion for men. Indeed, past research has found that structured interviews are fairly resistant to gender bias (Alonso et al, 2017; Kith et al, 2022; Pogrebtsova et al, 2020) overall; it appears that structure may also make the interview more resistant to differential effects of self-promotion tactics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found little or no gender bias in recruitment contexts when structured interviews or structured employment references are used [ 32 , 33 , 37 ]. The lack of variation in competence ratings and hiring decisions across targets in the studies presented here might be due to the structured information that participants received.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional FTF interviews are highly beneficial in gathering additional job‐relevant information beyond a resume about candidates during the selection process, in order to make judgments of employment suitability (Huffcutt & Arthur, 1994; Schmidt & Hunter, 1998). In addition, structured interview formats are relatively resistant to many types of biases, such a similarity between the applicant and interviewer in terms of gender or race/ethnicity (Kith et al, 2022; Levashina et al, 2014; McCarthy et al, 2010; Pogrebtsova et al, 2020). Technology‐mediated interviews like AVIs can offer improved efficiency for the initial screening process, particularly for positions with numerous applicants and/or with geographic challenges, such as when hiring out of region/country.…”
Section: Introductionmentioning
confidence: 99%